LINGUISTICAL SIGNIFICANCE OF PROVERBS ON THE TOPIC “MOTHERLAND” (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the linguistic and cultural content of the concept “Motherland” in Uzbek folk proverbs. Proverbs are studied as an important paremiological unit reflecting the historical memory, national values, and social thinking of the people. The study highlights the semantic, pragmatic, and cultural characteristics of proverbs on the topic “Motherland,” and analyzes the ways in which love for the motherland, loyalty, national unity, and spiritual values are expressed. Also, the role of proverbs in the formation of the national worldview and national mentality is revealed on the basis of a linguocultural approach. The results of the study show that the concept of "Homeland" occupies an important place in the national-cultural landscape of the Uzbek language and is manifested as a spiritual heritage transmitted from generation to generation through proverbs.